Aortic Z-scores in paediatric patients with marfan syndrome and other hereditary thoracic aortic diseases. (14th October 2021) - Eisfeld, M; Weiss, K; Yigitbasi, M; Pieske, B; Berger, F; Gehle, P
Abstract: Introduction: Marfan syndrome (MFS) and other hereditary thoracic aortic diseases (HTAD) are characterized by dilatation of the aorta caused by mutations in the FBN1-gene and other aortic genes. To prevent aortic dissection or rupture, patients are prophylactically treated by aortic surgery. Different z-scores of the aortic root are used for diagnosis and monitoring in paediatric patients. Purpose: What are the differences between the various aortic Z-scores in their use for monitoring, assessing the severity of the aortic disease, and establishing the indication for surgery in this age group? Methods: We retrospectively analyzed the diameters of aortic roots measured by echocardiography in 180 children and young adults (1 month to 25 years) with MFS and other HTADs presenting at our specialized outpatient clinic between January 2010 and August 2019. Thirteen patients underwent surgery during this period and 121 were monitored for a duration of one up to nine years. Five aortic z-scores were compared: Pettersen, Gautier, Cantinotti, Lopez, Boston. For evaluation of the severity of dilatation and indication for surgery, we used the last value before operation or the last follow-up value. For monitoring, we used the difference between the first and the last value. For comparison of the z-scores, values of the sinuses of Valsalva were analyzed. We investigated theoretic backgrounds and reference groups of each z-score. Results: The z-score values differ significantly (p<0, 001) for each score. The medians reach from 2.06 to 3.45, in operated patients 4.90 to 8.52, non-operated patients 1.86 to 3.31 (p<0, 001). 93 aortic diameters to 136 were classified as dilatated (z-score ≥2). There were significant differences of almost all z-scores in the comparison with one another. During follow-up, the increase of the median z-score ranged from 0.11 to 0.24, in operated patients from 0.73 to 1.93, in non-operated patients from 0.02 to 0.21, respectively. The median monitoring time was 4.14 years and 2.93 years, for patients monitored for more than one year and all patients, respectively. In the operated subgroup, a weak correlation showed that the longer the monitoring time and the closer the surgery arrived, the faster the z-scores rose. Lopez, Boston and Cantinotti have higher values and label a value quicker than dilatated, but also reveal the severity of dilatation and the potential necessity of surgery. Conclusions: Our data show that the various z-scores differ significantly. No z-score was superior regarding above-mentioned aspects, their differences in monitoring were small. However, it seems important to consistently use one same z-score. Expectedly, z-score values of each score were higher in the operated subgroup than in patients without surgery. However, there is no z-score value that determines a clear-cut indication for surgery. Funding Acknowledgement: Type of funding sources: None.